Lower gastrointestinal bleeding in pregnancy: Differential diagnosis, assessment and management. (September 2021) - Story, L; Rafique, S; Samadi, N; Mawdsley, J; Singh, B; Banerjee, A
Rectal bleeding is a common symptom experienced by pregnant women. Although the majority of cases are attributable to benign conditions such as haemorrhoids and anal fissures, other more serious diagnoses such as inflammatory bowel disease and malignancy should not be overlooked. Most investigations are safe during pregnancy and these should not be withheld as significant implications on both fetal and maternal morbidity may result. In these cases, a multidisciplinary team approach is essential. This review explores the differential diagnosis, investigation and management of rectal bleeding during pregnancy.